Analyzing the Role of Media Awareness in the Spread of Cat Scratch Disease Using a Fuzzy Fractional-Order Epidemic Model (Journal of Pure and Applied Sciences (Science Forum), 2025)
Cat Scratch Disease (CSD) is an emerging yet underreported zoonotic infection primarily caused by Bartonella henselae. Although it poses significant public health risks, particularly among immunocompromised individuals, it has received limited attention within the field of mathematical epidemiology. This study introduces a novel fuzzy fractional-order epidemic model to explore the impact of media awareness on mitigating the spread of CSD. The model employs Caputo-type fractional derivatives to capture memory-dependent transmission dynamics and incorporates fuzzy set theory to account for uncertainties in critical epidemiological parameters. A dedicated media awareness compartment is integrated into the framework, dynamically reducing the effective contact rate through behavioral change. The basic reproduction number R0R_0R0 is analytically derived using the next-generation matrix approach, and rigorous qualitative analysis establishes the existence, uniqueness, and stability of the system’s equilibria. Numerical experiments are conducted via the fuzzy Grünwald–Letnikov scheme with α-cut decomposition, providing robust approximations of system behavior. Simulation results reveal that sustained media interventions markedly reduce infection prevalence, flatten epidemic peaks, and delay outbreak progression. Overall, the findings highlight the crucial role of hygiene education and targeted communication strategies in managing zoonotic diseases. The proposed framework not only offers a more realistic and flexible tool for policy simulation but also holds promise for extension to other media-sensitive zoonoses, thereby contributing to improved epidemic preparedness and control.